Dietary supplements for aquatic sports - Derave, W.; Tipton, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Many athletes use dietary supplements, with use more prevalent among those competing at the highest level. Supplements are often self-prescribed, and their use is likely to be based on an inadequate understanding of the issues at stake. Supplementation with essential micronutrients may be useful when a diagnosed deficiency cannot be promptly and effectively corrected with food-based dietary solutions. When used in high doses, some supplements may do more harm than good: Iron supplementation, for example, is potentially harmful. There is good evidence from laboratory studies and some evidence from field studies to support health or per- formance benefits from appropriate use of a few supplements. The available evidence from studies of aquatic sports is small and is often contradictory. Evidence from elite performers is almost entirely absent, but some athletes may benefit from informed use of creatine, caffeine, and buffering agents. Poor quality assurance in some parts of the dietary supplements industry raises concerns about the safety of some products. Some do not contain the active ingredients listed on the label, and some contain toxic substances, including prescrip- tion drugs, that can cause health problems. Some supplements contain compounds that will cause an athlete to fail a doping test. Supplement quality assurance programs can reduce, but not entirely eliminate, this risk.